Politeness Strategies in Influencer Check-in Content on TikTok: A Pragmatic Study of Digital Consumer Interaction - Ni Putu Risma Rahma Dewi; Ni Made Diana Erfiani; Yohanes Octovianus Lesu Awololon; Putu Chrisma Dewi (Pusat riset dan Inovasi Nasional, 2026)
Effective communication is an important aspect in the hospitality industry as it affects the quality of service and guest satisfaction. The development of social media also makes hospitality services represented through digital platforms such as TikTok. This study aims to analyze the use of politeness strategies in TikTok content that displays the interaction between receptionists and guests during the hotel check-in process. The research uses a qualitative approach with a pragmatic discourse analysis method. The data consisted of 50 speeches obtained from five TikTok videos and an analysis based on Brown and Levinson's theory of politeness strategies. The results showed three types of politeness strategies, namely positive politeness, negative politeness, and bald on-record, while off-record strategies were not found. Positive politeness was the most dominant strategy, followed by negative politeness and bald on-record. The findings of the study show that the politeness strategy plays a role in building effective communication while representing the quality of hospitality services on social media. This research has implications for the development of pragmatic studies, especially regarding politeness strategies in hospitality communication in the digital environment.